Clinical and Immunological Factors Associated with Recommended Trough Levels of Adalimumab and Infliximab in Patients with Crohn’s Disease - Orts, Beatriz; Gutierrez, Ana; Madero, Lucía; Sempere, Laura; Frances, Ruben; Zapater, Pedro (Frontiers in Pharmacology, 2022)
Introduction: Up to 40% of patients with Crohn’s disease do not respond to treatment with anti-TNF or lose response after initial benefit. Low drug concentrations have been proposed as the main predictor of treatment failure. Our aim was to study the immunological profile and clinical evolution of patients with Crohn’s disease according to anti-TNF dose and serum through levels. Methods: Crohn’s disease patients in remission treated with infliximab or adalimumab at stable doses for at least for 3 months were included. Serum levels of anti-TNF, TNF-α, interferon-γ, and interleukin IL-12, IL-10, IL-26, were determined in blood samples taken just before drug administration. Patients were classified according to anti-TNF levels below, within or above target levels range and the use of intensified doses. Clinical evolution at 6 months was analyzed. Results: 62 patients treated with infliximab (8 on intensified schedule) and 49 treated with adalimumab (7 on intensified schedule) were included. All infliximab-treated patients showed levels within recommended range, but half of adalimumab-treated patients were below the recommended range. A negative significant relationship between body weight and adalimumab levels was observed, especially in patients treated with intensified doses. Higher median [IQR] values (pg/mL) of IL-10 (84.00[77.03-84.80] vs. 26.15[22.59-37.98]; p=0.0001) and lower values of interferon-γ (312.90[282.70-350.36] vs. 405.58[352.22-526.56]; p=0.0054) were measured in patients with levels of infliximab higher than 8 µg/mL compared to patients with in-range levels, whereas patients treated with intensified doses of infliximab showed significantly higher IL-26 levels than non-intensified patients (91.80[75.58-109.45] vs. 20.50[16.22-32.16]; p=0.0191), irrespective of serum drug levels. Patients with in-range levels of adalimumab showed higher values of IL-10 than patients with below-range levels (43.31[35.32-54.00] vs. 26.32[21.63-33.21]; p=0.0010). Patients treated with intensified vs regular doses of adalimumab had increased levels of IL-12 (612.30[570.20-1353.72] vs. 516.43[474.46-591.23]; p=0.0225). Four patients with low adalimumab levels (19%) and four treated with intensified doses were admitted to hospital during follow-up compared to none of the patients with levels within the range. Conclusion: patients with Crohn's disease treated with infliximab and adalimumab exhibit differences in serum levels of cytokines depending on the drug, dose intensification and steady state trough serum levels.